#TITLE_ALTERNATIVE# - HAQ (NIM: 20107047), NURUL
The relationship between predictors and response where response is nominal observation can be modeled by logit model. The result of Maximum likelihood estimation for it's parameters in logit model, is not explicit solutions. For that, the numerical method is required, such as by Newton-Raphson Method and Weighted Least Squares Method. This paper will study logit model rigorously. For case study, data of value academic potential test university students and civilian employment in certain period will be analyzed.